Mini-implants for orthodontic anchorage: Surface analysis after redrilling and sterilization - an in vitro study - Gross, J. M.; Nascimento, G. G.; Araújo, V. C.; Bönecker, M. J.S.; Furuse, C. [UNESP] (Jaypee Brothers Medical Publishing, 2016)
Objective: This study aimed to investigate, in vitro, possible alterations on mini-implants surface after retrieval and if the cleaning process and sterilization can predispose damages. Materials and methods: Two commercial mini-implants were tested for deformations after drilling and removing in artificial bone four times. Samples were analyzed by scanning electron microscopy, and surface alterations verified through thread and pitches deformation. To alterations caused by insertion/removal and the cleaning process and sterilization were verified in different procedures: Insertions and sterilization, only insertions, and only sterilization. Photomicrographs were analyzed in order to compare the surface characteristics. Head deformation was verified qualitatively. For a quantitative analysis, distances between threads were measured across the active part of the mini-implants. Results: No deformation was observed in both groups. The cleaning and sterilization processes did not provoke alteration in both groups. Nevertheless, the presence of synthetic bone was noted in some samples. The mean distances between implant threads were similar after all steps in all regions in both groups. Conclusion: The results suggest that the tested mini-implants can be retrieved without damage of its surface after four cycles of insertion, removal, and sterilization.
Keywords: Orthodontic mini-implant; Redrilling; Sterilization